Correlation of transthoracic echocardiography-derived pulmonary to systemic flow ratio with hemodynamically estimated left to right shunt in atrial septal defects - Erin Faherty; Hari Rajagopal; Simon Lee; Barry Love; Shubhika Srivastava; Ira A Parness; Santosh C Uppu (Wolters Kluwer Medknow Publications, 2022)
Background : Transthoracic echocardiographic (TTE) estimation of the pulmonary to systemic flow ratio (Qp/Qs) is routinely used in clinical practice and is included in the American Society of Echocardiography Guidelines. We sought to assess its real-world applicability with a particular focus on hemodynamically significant shunt lesions. Methods : Retrospective single institutional review of TTE's in patients with secundum atrial septal defect prior to cardiac catheterization (cath) from 2012 to 2018 was performed (n = 109), those with technically limited images for Qp/Qs calculation (n = 11) and those with time interval between TTE and cath >60 days were excluded (n = 14). Qp/Qs was calculated from stored clips by previously described methods and correlated with those obtained by oximetry. Patients were subdivided into two age groups <21 (Group 1) and ≥22 years (Group 2). TTE and cath methods for Qp/Qs estimation were compared using paired t-test, Pearson's correlation coefficient, and Bland-Altman plots. Results : Eighty-four subjects met inclusion criteria (age range 3-78 years). Group 1 n = 35; median age 10 years; Group 2 n = 49; median age 49 years. Transthoracic echocardiogram was performed 19.5 ± 15 days prior to cath. Mean Qp/Qs derived by cath and TTE were 2.09 ± 0.9 versus 2.54 ± 1.2 (P < 0.0001). Overall correlation was poor between the methods (r2 = 0.32, P < 0.0001) and continued to be poor for Groups 1 and 2 (r2 = 0.24, P = 0.003 and r2 = 0.40, P < 0.0001 respectively). Bland-Altman plots demonstrated poor agreement between the predetermined limits of agreement (-0.5-1.5). Conclusion : Transthoracic echocardiography estimated Qp/Qs, although routinely utilized in clinical practice, has poor correlation and agreement with oximetry-derived Qp/Qs. The test performs poorly in all age groups in detecting a hemodynamically significant shunt and tends to overestimate the degree of left to right shunt.